1994
DOI: 10.1111/j.1463-6395.1994.tb01206.x
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Origin of the Plasmodium of Rhopalura ophiocomae(Phylum Orthonectida)

Abstract: Adult orthonectids develop from germinal cells within a cytoplasmic matrix called a plasmodium. This is generally assumed to be formed by the parasite. In the case of Rhopalura ophiocomae, which lives in the brittle star Amphipholis squamata, the plasmodia occupying the perivisceral coelom are closely associated with the walls of the genital bursae or the gut, and they are covered by peritoneum. They have been reported to contain scattered small nuclei distinct from those within germinal cells, embryos, and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 1 publication
1
36
0
Order By: Relevance
“…Microvilli on the plasmodium surface are found in I. variabili (Slyusarev, Miller, 1998), as well as in Rhopalura ophiocomae and Ciliocincta sabellaria (Kozloff, 1994(Kozloff, , 1997. In all mentioned species, plasmodium bears microvilli in some separate parts only.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Microvilli on the plasmodium surface are found in I. variabili (Slyusarev, Miller, 1998), as well as in Rhopalura ophiocomae and Ciliocincta sabellaria (Kozloff, 1994(Kozloff, , 1997. In all mentioned species, plasmodium bears microvilli in some separate parts only.…”
Section: Discussionmentioning
confidence: 99%
“…The feeding strategy of the orthonectid plasmodium seems also to be similar to that of myxosporidian plasmodia (Uspenskaya, 1966(Uspenskaya, , 1984. It may be considered to be an indirect argument for that the plasmodium is an individual organism, but not a transformed host cell (tissue), as Kozloff (1994Kozloff ( , 1997 believed. Ðèñ.…”
Section: ðèñ 1 çðåëûé ïëàçìîäèé Intoshia Lineimentioning
confidence: 98%
See 2 more Smart Citations
“…They have been reported to parasitize acoels, platyhelminthes, annelids, molluscs, nemerteans, echinoderms, and chordates; and it has been suggested that they are present in the host animals as multinucleate plasmodia (Slyusarev and Miller, 1998). However, the plasmodia may also be a mass of host cells that has degenerated due to the parasites, and therefore not a viable stage of the orthonectid life cycle (Kozloff, 1994(Kozloff, , 1997. Male and female adults are produced from germinal cells within the plasmodia, and the ciliated adults swim out from the hosts.…”
Section: Introductionmentioning
confidence: 99%